2012
DOI: 10.1097/jto.0b013e31823c5c32
|View full text |Cite
|
Sign up to set email alerts
|

Worse Disease-Free Survival in Never-Smokers with ALK+ Lung Adenocarcinoma

Abstract: Introduction The EML4–anaplastic lymphoma kinase (ALK) translocation is a recognized oncogenic driver in non-small cell lung cancer. We investigated immunohistochemistry (IHC) screening with fluorescence in-situ hybridization (FISH) confirmation for ALK detection and estimated the prevalence of ALK-positivity in our patient cohort of never smokers, together with differences in clinical outcomes and prognostic factors for patients with ALK-positive and ALK-negative tumors. Methods We designed a three-phase st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
84
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 26 publications
11
84
0
1
Order By: Relevance
“…There is limited data on the prognosis of ALK + patients in the absence of ALK TKI treatment. Whereas 1 study suggested similar outcomes [24], another study indicated potentially inferior survival [25], which would support our observation of a potentially more aggressive (metabolically active) disease resulting in an increased SUV max . Our findings of a more aggressive tumour biology of ALK + NSCLC are supported by previous observations: ALK + NSCLC tends to occur in younger patients and those with more advanced disease while this relationship has not been reported for EGFR + NSCLC [26,27].…”
Section: Discussionsupporting
confidence: 60%
“…There is limited data on the prognosis of ALK + patients in the absence of ALK TKI treatment. Whereas 1 study suggested similar outcomes [24], another study indicated potentially inferior survival [25], which would support our observation of a potentially more aggressive (metabolically active) disease resulting in an increased SUV max . Our findings of a more aggressive tumour biology of ALK + NSCLC are supported by previous observations: ALK + NSCLC tends to occur in younger patients and those with more advanced disease while this relationship has not been reported for EGFR + NSCLC [26,27].…”
Section: Discussionsupporting
confidence: 60%
“…On the other hand, Kim et al were able to demonstrate that patients with ALK-rearranged NSCLC had a significant worse OS outcomes after factoring in age, sex, histology, stage, and performance status [103]. Similarly, Yang et al found that EML4-ALK status is a poor prognostic factor for relapse-free survival after factoring in stage, sex, age, and treatment [104].…”
Section: Clinicopathologic Characteristics Of In Patients With Alk-rementioning
confidence: 91%
“…Point mutations and multiple alk gene copies have been detected in neuroblastomas6 and inversions (eg, EML4-ALK) in a subset of non-small cell lung carcinomas (NSCLCs) 7. alk gene translocations have been associated with the subcellular topography of ALK protein detected by immunohistochemistry8 and can also be assessed with high specificity and sensitivity using fluorescent in situ hybridisation (FISH) 9 10…”
Section: Introductionmentioning
confidence: 99%